Conorfamide-Sr3, a structurally novel specific inhibitor of the Shaker K+ channel. (November 2017) - Campos-Lira, Elba; Carrillo, Elisa; Aguilar, Manuel B.; Gajewiak, Joanna; Gómez-Lagunas, Froylán; López-Vera, Estuardo
Abstract: Conorfamides (CNFs) are toxins initially characterized from the venom duct of the venomous marine snail Conus spurius from the Gulf of Mexico; at their C-termini, these toxins are amidated and have high sequence similarity with the molluskan cardioexcitatory tetrapeptide Phe-Met-Arg-Phe-NH2 (FMRFamide or FMRFa) and other FMRFa-related peptides (FaRPs) found in the five molluskan classes, and in other invertebrate and vertebrate phyla. These peptides were the first FaRPs found to be present in any venom, and they are biologically active in mice, limpets, and/or freshwater snails. However, the molecular targets of the known CNFs (CNF-Sr1 and CNF-Sr2 from C . spurius, and CNF-Vc1 from C . victoriae ) remain unidentified. Very recently, three FaRPs from C. textile have been found to potentiate the currents of acid-sensing ion channels. In this work, we characterized a novel conorfamide, CNF-Sr3 (ATSGPMGWLPVFYRF-NH2 ), comprised of 15 amino acid residues, and with a specific blocking activity for the Shaker subtype of the voltage-gated potassium channels, without significant effect on the Shab, Shaw, Shal and Eag channels. This peptide is the third type of disulfide-free conotoxins that has been discovered to target K + channels. Highlights: A novel conorfamide, CNF-Sr3, was discovered from the venom of Conus spurius . Among the voltage-gated potassium channels CNF-Sr3 blocks Shaker but not Shab, Shaw, Shal, and Eag . CNF-Sr3 is a new molecular tool for studying the Shaker family.